HAKIKAT PROFESI KEGURUAN DITINJAU DARI SUDUT PANDANGAN UNDANG-UNDANG PENDIDIKAN - Lubis Pebariani Lubis (Tazkiya: Jurnal Pendidikan Islam, 2026)
The teaching profession plays a pivotal role in shaping the intellectual, moral, and social development of a nation. In Indonesia, this profession is legally recognized and regulated through comprehensive educational laws, notably Law No. 20 of 2003 on the National Education System and Law No. 14 of 2005 on Teachers and Lecturers. These laws define teachers not merely as instructors but as professional educators entrusted with ethical responsibilities, pedagogical competencies, and transformative societal roles. This article examines the philosophical, juridical, and sociological dimensions of the teaching profession as framed by national legislation. Through a normative legal approach and literature analysis, the study highlights how legal instruments elevate the status of teachers and reinforce their role as agents of character building and national progress. The findings emphasize the need for continuous professional development, ethical integrity, and legal protection to sustain the quality and dignity of the teaching profession in the modern educational landscape.